Al-Istiqomah Islamic Boarding School Academic Information System Based on the Waterfall Model - Thoha Firdaus; Muhammad Iksannudin; Muhammad Naufal Jamil Al Basyari Sutoyo; Deri Feriyansah; Pamuji Muhamad Jakak (Jurnal Ilmiah Informatika dan Komputer, 2025)
This article discusses the development of a web-based Academic Information System (AIS) for Istiqomah Islamic Boarding School using  the Laravel framework. The main objective of this study is to create an integrated and efficient system to manage student academic data, including grades, report cards, attendance, and information about both instructors and students at Al-Istiqomah Islamic Boarding School. The research method used is Research and Development (R&D) with a waterfall approach, starting from requirements analysis, system design, implementation, and testing. Data collection was carried out through interviews with pesantren administrative staff and observation of ongoing academic processes. The findings of the study show that the AIS developed successfully facilitates the digital management of academic data, reducing reliance on manual note-taking, which is prone to errors and slow. The system provides essential modules such as student data management, grade input, attendance recapitulation, student financial reports, and class schedules. System testing using the black box testing method  shows that all functions are operating well and meeting the needs of the user. Thus, this system is expected to increase efficiency and accuracy in the management of academic information, as well as support better decision-making at the Istiqomah Islamic Boarding School.